The Dynamics of Regional Trade Agreements: Indonesia’s Policy Responses to RCEP - Septiana Sari; Budi Santoso (Sosiora, 2020)
Regional Comprehensive Economic and Partnership (RCEP) is an international agreement consisting of ASEAN and Non-ASEAN countries (Australia, China, Japan, New Zealand, and South Korea). It could positively or negatively impact the Indonesian economy, so it is necessary to conduct a preliminary assessment after Indonesia signs the Agreement. This research uses the normative judicial method by conducting a literature study. This research uses primary and secondary legal material and uses secondary data. This descriptive-analytical research explains the Regional Comprehensive Economic and Partnership Agreement provisions by linking them to the basis of Indonesian law. RCEP is used to expand and deepen ASEAN’s involvement with five Non-ASEAN countries. RCEP can strengthen trade relations between its members by reducing tariffs, including export and import relations. RCEP can increase the value of an investor’s foreign investment in Indonesia. MSMEs are a form of economy that has an essential role in the Indonesian economy and has room in the RCEP agreement. As a multilateral agreement, conflict and economic inequalities between members are possible. Therefore, Indonesia must carefully consider the steps.